Short Term (14 Days) Consumption of Insoluble Wheat Bran Fibre-Containing Breakfast Cereals Improves Subjective Digestive Feelings, General Wellbeing and Bowel Function in a Dose Dependent Manner - Lawton, Clare; Walton, Jenny; Hoyland, Alexa; Howarth, Elaine; Allan, Peter; Chesters, David; Dye, Louise (Nutrients, 2013)
This study investigated whether increasing insoluble (predominantly wheat bran) fibre over 14 days improves subjective digestive feelings, general wellbeing and bowel function. A single centre, multi-site, open, within subjects design with a 14 day non-intervention (baseline) monitoring period followed by a 14 day fibre consumption (intervention) period was performed. 153 low fibre consumers (<15 g/day AOAC 985.29) completed a daily symptom diary for 14 days after which they consumed one bowl of ready-to-eat breakfast cereal containing at least 5.4 g fibre (3.5 g from wheat bran) for 14 days and completed a daily symptom diary. Significant improvements were demonstrated in subjective perception of bowel function (e.g., ease of defecation) and digestive feelings (bloating, constipation, feeling sluggish and digestive discomfort). Significant improvements were also found in subjective perception of general wellbeing (feeling less fat, more mentally alert, slim, happy and energetic whilst experiencing less stress, mental and physical tiredness, difficulty concentrating and fewer headaches). In general, improvements in study outcomes increased with increasing cereal/fibre consumption. However, consuming an additional minimum 5.4 g of fibre (3.5 g wheat bran) per day was shown to deliver measurable and significant benefits for digestive health, comfort and wellbeing. Encouraging consumption of relatively small amounts of wheat bran could also provide an effective method of increasing overall fibre consumption.